Transient injuries are a problem in field hockey: A prospective one-season cohort study - Rees, H.; Shrier, I.; McCarthy Persson, U.; Delahunt, E.; Boreham, C.; Blake, C. (Translational Sports Medicine, 2020)
Injury definitions encompass all physical complaints, medical attention, and time loss. Expressing injury burden in terms of short- and long-term impact on athlete performance may be meaningful for coaches in terms of preparation. Therefore, our aim was to describe transient (symptoms <7 days) and substantial (symptoms =7 days) injuries suffered in field hockey throughout the Irish Hockey League (IHL). Following ethical approval, participants were assigned unique accounts to record injuries through a monitoring software. An all physical complaints definition was adopted. Team physiotherapists were contacted weekly to further capture and corroborate details on injuries. Transient and substantial injury classifications were applied. A total of 173 injuries in 14 690 exposure hours (11.8/1000 h) occurred. Incidence of medical attention (n = 119) and time-loss (n = 70) injuries was 8.1/1000 h and 4.8/1000 h. Teams suffered transient injuries every 2.3 weeks (median = 2, IQR = 4) at a rate of 6.3/1000 h and substantial injuries every 2.5 weeks (median = 1.5, IQR = 3.25) at a rate of 5.5/1000 h. The lower back and knee were common transient injuries (7.5%), with the hamstring a common substantial injury (11.6%). Although many field hockey injuries are substantial, transient injuries are equally as frequent. These additional means of classifying injuries inform teams of the injuries that will cause disruption within their squad.